Horos Dios : An Athenian Shrine and Cult of Zeus - Lalonde, Gerald (Monumenta Graeca et Romana, 2006)
In five chapters this volume 1) offers new evidence for the form, date, and meaning of an Archaic rupestral horos of Zeus on the Hill of the Nymphs in Athens, 2) reports and interprets for the first time many rock cuttings as remnants of the shrine of Zeus implied by the horos inscription, 3) argues from scattered artifacts of Zeus found in central and western Athens and from comparative archaeological evidence that this shrine was devoted primarily to the popular cult of Zeus Meilichios, 4) presents evidence and arguments that other deities, including Herakles Alexikakos, were worshipped at this shrine, and 5) summarizes the chronology of this cult and shrine in their historical and topographical contexts. An Appendix assembles all the testimonia to Zeus Meilichios in Attica.